An observational study examining the correlation between finger dexterity and attention in the dominant hand among young adults - K., Megha; K. B., Riyas Basheer; Rai, Subhashchandra; Pinto, Royline Fathima (International Journal of Research in Medical Sciences, 2025)
Background: Finger dexterity and attention are essential components of cognitive-motor functioning, influencing daily activities such as writing, grasping objects and executing precise movements. While previous research has examined cognitive-motor relationships in older adults, studies focusing on young adults remain limited. Given the increasing demands on attention and manual coordination in academic, professional and sports-related domains, understanding their interdependence is crucial. To assess finger dexterity using the Nine-Hole Peg Board Test (NHPT), to evaluate attention regulation using the Attention Control Scale (ACS) and to determine the correlation between attention control and manual dexterity in the dominant hand. Methods: A cross-sectional observational study was conducted with 100 healthy young adults aged 18–25 years at educational Institution, Mangalore. Participants’ dominant hand was identified using the Hit-the-Dot Test, followed by assessments of attention (ACS) and dexterity (NHPT). Data were analysed using Pearson’s correlation, with statistical significance set at p<0.05. Results: Among participants, 38% were males and 62% were females, with a mean age of 19.04±1.46 years. Pearson’s correlation analysis revealed a strong positive association between attention scores and dexterity performance (r=0.878, p=0.001), indicating that individuals with higher attention control exhibited superior finger dexterity. Conclusions: This study establishes a significant correlation between attention and finger dexterity, reinforcing the cognitive-motor connection in young adults. The findings highlight the importance of attentional regulation in executing fine motor tasks, with potential applications in fields such as surgery, sports and rehabilitation field.